Gastroentero-histopathology Studies of Synthesized Naproxen Esters in Young Healthy Sprague-Dawley Rat Model - Akter, Mansura; Saha, Sajal Kumar; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Naproxen and its synthesized esters namely naproxen methyl ester, C15H16O3 (compound 1), ethyl ester, C16H17O3 (compound 2) and isopropyl ester, C17H20O3 (compound 3) were subjected to NSAID induced gastro-ulcergenecity studies on young, healthy male rat model. Rats (Rattus novergicus: Sprague-Dawley strain) of 2-months old weighing 95105 g were administered with naproxen (10 mg/kg b.w.) compound 1 (10.609 mg/kg b.w.), compound 2 (11.217 mg/kg b.w.) and compound 3 (11.826 mg/kg b.w.) twice daily for 4.5 days. The naproxen esters appeared to induce significantly less GI injury and bleeding both in microscopic and macroscopic examinations. This study can be a basis of reference for further acute, chronic or subchronic toxicity studies in various in-vivo models. Dhaka Univ. J. Pharm. Sci. 14(1): 49-53, 2015 (June)